Makna Pesan Motivasi Pantang Menyerah dalam Lirik Lagu - Shinta Kristanty; Jasmine Ramadhani Karim; Mulyati; Liza Dwi Ratna Dewi (Pantarei, 2026)
This study aims to examine the meaning of perseverance motivation messages contained in the lyrics of the song "Grow Up" by Stray Kids. This research employs a qualitative approach using a constructivist paradigm. The research method applied is Ferdinand de Saussure's semiotic theory, which focuses on the relationship between the signifier and the signified in constructing meaning. The findings indicate that the song "Grow Up" conveys strong messages of perseverance motivation. These meanings are reflected in lyrics that emphasize that failure, mistakes, and feeling of being left behind are natural parts of the growing process. The song highlights the importance of self-acceptance, patience in personal growth, and the belief that everyone has their own pace and path in life. In addition, the consistent emotional support expressed in the lyrics suggest that individuals are not alone in facing life's challenges. Overall, "Grow Up" represents a form of motivational communication that is comforting and empowering, especially for young listeners who are experiencing mental pressure or uncertainty in life. This study is expected to contribute to a deeper understanding of song lyrics as a form of mass communication in delivering motivational messages and supporting mental well-being.